Protective effect of naringin against oxaliplatin‐induced peripheral neuropathy in rats: A behavioral and molecular study. Issue 9 (7th June 2022) - Semis, Halil S.; Kandemir, Fatih M.; Caglayan, Cuneyt; Kaynar, Ozgur; Genc, Aydın; Arıkan, Sefik M.
Abstract: Oxaliplatin (OXL) is a chemotherapeutic drug used for metastatic and other types of cancer, but it causes peripheral neuropathy as a dose‐limiting side effect. Herein, we used the rat model of OXL‐induced peripheral neuropathy to demonstrate the protective effects of naringin (NRG) in this neuropathy. In this study, rats were injected with OXL (4 mg/kg, body weight, i.p.) in 5% glucose solution 30 min after oral administration of NRG (50 and 100 mg/kg, body weight) on the 1st, 2nd, 5th, and 6th days. OXL caused sensory and motor neuropathy (as revealed by the hot plate, tail flick, rota‐rod, and cold hyperalgesia tests) in the sciatic nerve of rats. Coadministration of oral NRG alleviated OXL‐induced sensory and motor neuropathy. Levels of superoxide dismutase, catalase, glutathione peroxidase, nuclear factor erythroid 2‐related factor 2, Heme oxygenase‐1, nuclear factor‐κ B, tumor necrosis factor‐α, interleukin‐1β, Bax, Bcl‐2, caspase‐3, paraoxonase, mitogen‐activated protein kinase 14, neuronal nitric oxide synthase (nNOS), acetylcholinesterase, and arginase 2 in the sciatic nerve tissues were assessed by real‐time polymerase chain reaction. Moreover, the protein levels of caspase‐3, Bax, Bcl‐2, intercellular adhesion molecules‐1, glial fibrillary acidic protein, and nNOS were examined by Western blot analysis. NRG treatment significantly improved all the above‐mentioned parameters and reduced OXL‐induced oxidative stress, inflammation, and apoptosis in the sciatic nerve tissue. In conclusion, this study demonstrated that NRG significantly attenuated OXL‐induced peripheral neuropathy and might be considered as a new protective agent to prevent the OXL‐induced peripheral neuropathy.